Analisis Kinerja Keuangan Perbankan pada Bank Umum Syariah di Indonesia - Dila Ardila; Isni Andriana; Reza Ghasarma (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
The purpose of this study was determine and analyze the financial performance of Islamic Banks in Indonesia. The study used quantitative data type by using secondary data as the data source. Data type by using secondary data as the data source. The sample used in this research is 9 islamic commercial banks that’s was selected using purposive sampling method from a total population of 14 registered in Financial Service Authority from the period 2014-2018. The analytical technique used is descriptive analysis using the RGEC method: Risk Profile is measured using NPF and FDR ratio, Good Corporate Governance (GCG), Earnings is measured using ROA and BOPO ratio, and Capital is measured using KPMM ratio. The result showed that the NPF ratio in good category, FDR ratio in pretty good category, GCG in good category, ROA ratio in bad category, BOPO ratio in not good category and KPMM ratio in very good category. Keywords: analyze the financial performance, Islamic banks, Indonesia